VFR Tourism and the Tourist Gaze: Overseas Migrant Perceptions of Home. (24th January 2017) - Huang, Wei‐Jue; King, Brian; Suntikul, Wantanee
Abstract: Visiting friends and relatives travellers have personal connections with their homeland, which influence how they gaze upon its people, cultures and landscapes. This study examines the perceptions of children of immigrants towards visiting their ethnic homeland. The tourist gaze provides a theoretical framework to analyse their experiences when navigating dichotomies between home and away and between the self and others during their travels. Findings revealed that rather than gazing at the exotic 'other', they are seeking out similarities which allow for a greater connectedness with family and heritage. They also explained problems and issues that they encountered, as a consequence of feeling obliged to defend their homeland. Copyright © 2017 John Wiley & Sons, Ltd.